Kesiapan Dinas Komunikasi, Informatika Dan Persandian Kota Yogyakarta Dalam Mendukung Implementasi Smart City Di Pemerintah Kota Yogyakarta - Sah, Suciati; Suhartono, Suhartono (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2018)
Dinas Komunikasi, Informasi, dan Persandian Yogyakarta is a combination of 3 assignments used to be handled by 4 different divisions : (1) Telematics and Information Technology, (2) Promotion, Publication, and Public Relation, (3) Coding, and (4) Sectorial Statistics. The merging of those 4 divisions weren’t followed byaddition of resources. All human resources, equipment, and technical rules used are those already available at the time. Based on Yogyakarta’s Mayor’s Rules number 79 year 2016 about Organization Structure, Position, Duties, Function, and Working Procedures of Dinas Komunikasi, Informasi, dan Persandian Yogyakarta, the duty of Dinas Komunikasi, Informasi, dan Persandian is to carry out regional governmentmatters based on the principle of regional autonomy in communication, information, coding, and statistics area. Dinas Komunikasi, Informasi, dan Persandian Yogyakarta must have some strategies in order to carry out its duties and functions, especially to support the acceleration of implementation of smart city for Yogyakarta City Government. Some matters that need to be prepared in order to support the programare (1) Human Resources who are competent in information technology (e-skills) and implementation of electronic based services concepts, (2) Infrastructures of communication and information technology which include infrastructures for network & data centre, information system, and data integration & integrated application development.